2015
DOI: 10.5433/1679-0359.2015v36n2p1099
|View full text |Cite
|
Sign up to set email alerts
|

Substituição do farelo de soja pela torta de babaçu em rações para frangos de corte dos 22 aos 42 dias de idade

Abstract: ResumoO objetivo deste trabalho foi avaliar a viabilidade técnica e econômica da substituição parcial do farelo de soja pela torta de babaçu em rações para frangos de corte dos 22 aos 42 dias de idade. Foram utilizados 80 frangos Cobb 500 ® , distribuídos em delineamento inteiramente casualizado, com quatro tratamentos (0, 10, 20 e 30% de substituição do farelo de soja pela torta de babaçu) e cinco repetições de quatro aves. Foram avaliados o desempenho (ganho de peso, consumo de ração e conversão alimentar), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
2
2
1
Order By: Relevance
“…These results differ from those found by Silva et al (2015), by replacing soybean meal with babassu bagasse in rations for broilers from 22 to 42 days of age. They did not observe differences between treatments levels.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results differ from those found by Silva et al (2015), by replacing soybean meal with babassu bagasse in rations for broilers from 22 to 42 days of age. They did not observe differences between treatments levels.…”
Section: Discussioncontrasting
confidence: 99%
“…Possibly these results occurred due to the absence of essential amino acids in the coconut bagasse, which is not the case with the licuri bagasse used in this research (Thomas and Scott., 1962).In broilers that had their corn partially replaced by cassava bagasse, values close to 2.00 were observed for feed conversion and approximate values of the present research for weight gain, being considered good results for the species, corroborating with statements made on the quality of licuri bagasse for feeding these animals (NASCIMENTO et al, 2005).The variables, weight gain, feed conversion and feed intake did not show significant differences in broilers during the growth phase, when fed with increasing levels of babassu bagasse in the diet, similar results to those found in this research, which allows to infer that at this stage the use of alternative sources of food from oilseeds does not interfere with the zootechnical performance of the animals, as long as they are used in the correct dosages (SILVA et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…However, there was an increasing linear response in the GRW (%), according to the equation GRW (%) = 2.154 + 0.012 BP (r 2 = 0.81). Similarly, Silva et al (2015b), who evaluated the effect of replacing soybean meal by BP (0,10,20,or 30%) in the rations of Cobb 500 strain broiler chickens, observed that the gizzard relative weight increased linearly due to the increase in fiber content, which corroborates our own results.…”
Section: )supporting
confidence: 79%
“…Similarly, Silva et al (2015b) found that the levels of substitution of soybean meal with babassu pie did not affect carcass, thigh, quarter, and breast yields in sacrificed chickens at 42 days of age, indicating that babassu pie can substitute up to 30% of the soybean meal in the rations (corresponding to a level of 8.4% of BP), provided these meet the nutritional requirements of the birds.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation